The use of electron accelerators for simulation of radiation damage in rock salt considered for safe storage of nuclear waste - Dubinko, V.I.; Dovbnya, A.N.; Borisenko, V.N.; Petrusenko, Yu.T.; Grytsyna, V.M.; Sugonyako, A.V.; Vainshtein, D.I.; den Hartog, H.W. (Вопросы атомной науки и техники, 2006)
Rock salt is one of the considered storage mediums for nuclear high level waste (HLW), and so the behavior of rock salt in the vicinity of HLW is of great practical interest. The main contribution to the irradiation from a radioactive waste comes from gamma-radiation, which requires a comparison of its action with that of the electron irradiation, widely used for simulation of radiation damage in rock salt. To solve this problem, we have used a linear electron accelerator to produce bremsstrahlung gamma-radiation spectrum similar to the real spectrum of HLW. Samples of synthetic crystals of NaCl have been γ- irradiated up to the dose ranging from 1.2 10⁸ Gy to 7.8 10⁸ Gy and subsequently investigated by means of differential scanning calorimetry and atomic force microscopy. Electron and gamma irradiated samples have shown a comparable damage concentration and the structure of the radiolytic products, which justifies the use of electron irradiation for the imitation of radiation damage in the vicinity of HLW.